Signatures of B Cell Receptor Repertoire Following Pneumocystis Infection - Sun, Han; Yang, Hu-Qin; Zhai, Kan; Tong, Zhao-Hui (Frontiers in Microbiology, 2021)
B cells play vital roles in host defense against Pneumocystis infection. However, the features of the B cell receptor (BCR) repertoire in disease progression remain unclear. Here, we integrated single-cell RNA sequencing and single-cell BCR sequencing of immune cells from mouse lungs in an uninfected state and 1–4 weeks post-infection in order to illustrate the dynamic nature of B cell responses during Pneumocystis infection. We identified continuously increased plasma cells and an elevated ratio of (IgA + IgG) to (IgD + IgM) after infection. Moreover, Pneumocystis infection was associated with an increasing naïve B subset characterized by elevated expression of the transcription factor ATF3. The proportion of clonal expanded cells progressively increased, while BCR diversity decreased. Plasma cells exhibited higher levels of somatic hypermutation than naïve B cells. Biased usage of V(D)J genes was observed, and the usage frequency of IGHV9-3 rose. Overall, these results present a detailed atlas of B cell transcriptional changes and BCR repertoire features in the context of Pneumocystis infection, which provides valuable information for finding diagnostic biomarkers and developing potential immunotherapeutic targets.